Sugar cane burning and human health: An analysis using spatial difference in difference - Andre Chagas; Alex Almeida; Carlos Azzoni (European Regional Science Association (ERSA), 2013)
The production of ethanol and sugar from sugar cane has sharply increased for the last 20 years. If there are overall incentives to substitute the consumption of fossil fuels by biofuels, the increase of production and the expansion of new cultivated areas of sugar cane have eventually an impact on human health and employment mainly at regional levels. To harvest the crop–mostly manually done by low-skill workers–the practice of burning to clean dry grasses and poisonous insects has been executed for years during the dry season, what increase the productivity of workers. However, the burning generates a massive quantity of smoke that spread in the region reaching cities and becoming a potential threat to the human health. For example, many studies have linked the straw burning of sugarcane with respiratory diseases in the producing regions. Due to this, in the state of Sao Paulo, the largest sugarcane's producer in Brazil ? the state is responsible for 60% of total production, but only 25% the mechanized harvest are mechanized – a law was approved, in 2002, to enforce sugar cane mills to completely stop the burning of sugar cane before the harvest until 2030. The main objective of this paper is to investigate the impact of the burning prohibition of sugar cane on respiratory problems of children, teenagers and elderly people. This analysis focuses also on other socio-economic determinants such as GDP, demographic density, job opportunities, and Human Development Index of municipalities for which sugar cane activity plays an important role economically. With a recent methodology developed based on spatial propensity score matching we compare municipalities where burning is still going on with those where are not. We try to capture the socio-economic interactions among the agents in their interrelated economic system through spatial analysis. The data used in this study corresponds to a balanced panel of 645 municipalities from 2002 to 2007 where the geographic coordinates of burning occur, morbidity and other economic indicators are available.
Keywords: C14; C21; Q18; 330; Sugar Cane Burning; Health Condition; Spatial Econometrics